Preparation and enhanced electrorheological properties of elastomers filled with rod-shaped TiO2 particles - Ti, Gang; Fan, Yi; Tang, Jian; Niu, Chenguang; Xiong, Xiaoyan (Frontiers in Materials, 2023)
The morphology of dispersed particles has been proven to have a significant impact on performance of electrorheological (ER) materials, while there is a lack of relevant research on its impact on the properties of electrorheological elastomers (EREs). In this study, the TiO2 particles with spherical, short rod, and long rod shape were fabricated with sol-gel method, and the EREs were prepared with these three kinds of particles as dispersion phase. Particle characterization results show that the rodshape TiO2 particles with larger average size exhibit a combination of anatase and brookite phase. The viscoelastic properties of three types of EREs under varying strain amplitude and shear frequency were tested. The results indicate that the long rod-shape TiO2 particles filled EREs shows higher storage modulus G' and higher relative ER effect within the electric field from 0 to 3 kV/mm. The observations indicate the use of rod-shape TiO2 particles in the form of brookite phase may help enhance the ER properties of elastomers. The investigation contributes to the designing, preparation, and application of anisotropic ERE.